BRICS Expansion and Future Prospects - Muhammad Ijaz Khan; Shokat Hayat (Journal of BRICS Studies)
The BRICS (Brazil, Russia, India, China, South Africa) bloc, representing a coalition of major developing nations, has recently expanded by admitting six new members—Argentina, Egypt, Ethiopia, Iran, Saudi Arabia, and the UAE—effective from January 1, 2024. This expansion transforms the bloc into BRICS Plus (+), reflecting the rising multipolarity in global politics and economics. This paper examines the implications of BRICS Plus for Pakistan, assessing potential economic, geopolitical, and security benefits while addressing challenges such as Indian opposition and Western pressure. The study concludes with policy recommendations for Pakistan to leverage this opportunity by enhancing trade, investment, and diplomatic relations within BRICS.